Assessing the prevalence of gendered ageism among long-term care employees - Loy-Ashe, Tarah; Hawkins, Brent; Puymbroeck, Marieke Van; Lewis, Stephen; Hays, Antionette (Journal of Long-Term Care, 2024)
Ageism, discrimination based on age, particularly against older adults, intersects with other forms of discrimination, including sexism. In long-term care settings, gendered ageism can manifest in various ways, influencing both the quality and type of care older adults receive based on their gender. Understanding and addressing ageism in these settings is essential to ensuring the dignity, respect, and quality of life for older adults. The purpose of this mixed methods study was to explore long-term care (LTC) employees’ attitudes towards age and gender. A theoretical framework of feminist disability theory and compulsory youthfulness allows for an intersectional critique of ageism, sexism, and ableism and how each contributes to the oppression of long-living adults (age 80 and over) and disabled long-living adults. Triangulation of data was achieved through surveys, interviews, and artifacts. Sixty employees completed an on-line survey consisting of demographic questions (age, race, gender, years employed in LTC, highest level of education, employment) and the Fraboni Scale of Ageism during the Coronavirus pandemic between August 21, 2020 and September 22, 2020. Data were analyzed using an independent samples t-test, One Way ANOVA, and One Sample Median Test. Twenty-one of these employees also participated in a phone interview during the time period of survey collection. Interview data were analyzed using open coding, axial coding, then thematic analysis. Cultural artifacts available to the primary researcher, and relating to the study, were noted. Considering the primary researcher was not allowed to enter the facility, the types of artifacts collected included social media posts via Twitter, Facebook, and the organization’s blog. Blog and social media posts ranged from September 1, 2020 to February 1, 2021. Mixing of qualitative and quantitative data was completed for the final results by merging them via side by side comparison table. Quantitative findings indicated there was a statistical difference in FSA scores for younger adults (M = 49.33, SD = 6.08), adults (M = 52.97, SD = 8.66), and older adults (M = 46.76, SD = 7.85). Middle age adults had significantly higher FSA scores than younger adults and older adults. Qualitative data provided the strongest connection that sexist and ageist attitudes exist among employees as it demonstrated that some employees had different expectations of residents based on the residents’ gender. A review of social media and policy artifacts concluded there was no resident perspective present in research topics, research trials, blog posts, or community events. Overall, findings indicated employees’ interactions with, and attitudes towards, residents were influenced by themes of compassionate ageism, ableism, and identity, which resulted in meta-theme caregiver validation and reward. Although most employees felt a deep connection with residents, they detached themselves from the aging process, instead seeking affirmation and recognition from residents through gratitude and positive interactions. Results from this study indicated certain power dynamics and suggested that employees actively sought positive care interactions with residents. Most employees preferred to care for residents who appeared to need assistance, were appreciative, and interacted with the employee in a positive way. When this occurred, employees enjoyed relationships with these residents and caring for them on a continuous basis. Essentially, employees preferred to care for someone who conformed to that employee’s expectations for care.
Keywords: dept.hls; peer-reviewed

Answering the Big Questions About Play - Kuhaneck, Heather; O'Brien, K. (Making Play Just Right: Unleashing the Power of Play in Occupational Therapy, 2022)
Keywords: dept.hls

Neurodivergence is also an LGBTQ+ topic: Making space for “neuroqueering” in the outdoors - Loy-Ashe, Tarah (Parks Stewardship Forum, 2023)
Recently, the field of research exploring the links between neurodivergence and the LGBTQ+ community has grown. Many queer adults who were not diagnosed as children are just now receiving neurodivergent diagnoses. Nick Walker coined the term “neuroqueer” in 2015 to describe the intersection of being both neurodivergent and queer. “Neuroqueering” refers to the embodying and expressing of one’s neurodivergence in ways that also queer one’s performance of gender, sexuality, ethnicity, and/or other aspects of one’s identity (Walker 2021). Considering the increase of queer representation in the outdoors, it is necessary to also address neuroqueering and its implications for the outdoor community. This conceptual article will address the connection between neurodivergence and the LGBTQ+ community, implications for the queer outdoors, and ways to include neuroqueer recreationalists and outdoor advocates in efforts to make the outdoors more equitable.
Keywords: dept.hls

Intersections of ageism and gender stigma: Exploring long-term care employees' attitudes towards aging - Loy-Ashe, Tarah; Hawkins, Brent (Innovation in Aging, 2021)
The purpose of this mixed methods, single case study was to explore long-term care (LTC) employees’ attitudes towards age and gender. The intersection of Rosemary Garland-Thomson’s theory of feminist disability (2001) and Hailee Gibbons’ ...
Keywords: dept.hls; peer-reviewed

The rise of compassionate ageism: Long-term care employees’ attitudes toward aging during COVID-19 - Loy-Ashe, Tarah; Hawkins, Brent L.; Puymbroeck, Marieke Van; Lewis, Stephen T.; Hays, Antoinette M. (American Journal of Recreation Therapy, 2022)
Objectives: Research suggests that ageist beliefs and behaviors have increased since the onset of the novel coronavirus 2019 (COVID-19). Considering that COVID-19 has taken a particularly heavy toll on long-term care (LTC) residents, this study examined if LTC employee perceptions of aging were influenced by working in a LTC facility during the pandemic.Methods: Qualitative data collection included 30-minute interviews with 21 LTC employees in the Boston, Massachusetts, area including 10 nurses, three nursing assistants, four clinical coordinators, two social workers, one recreation therapist, and one registered dietitian.Results: An increase in perceptions and behaviors representative of compassionate ageism (CA) was self-reported among participants.Discussion: The current study demonstrates how an increase in CA among employees was perpetuated by the COVID-19 pandemic. Allied health and nursing professionals should be mindful of attitudes toward aging, and how health events can reinforce ageist beliefs and behaviors. Opportunities for recreation therapists to lead antiageist efforts in LTC are identified.
Keywords: COVID-19; aging; compassionate ageism; dept.hls; long-term care; peer-reviewed; recreational therapy; ⚠️ Invalid DOI

Lessons learned from COVID-19: Being known in online social work classrooms - Smoyer, Amy B; O’Brien, Kyle; Rodriguez-Keyes, Elizabeth (International Social Work, 2020)
This article presents findings from a survey of undergraduate social work (Bachelor of Social Work [BSW]) students about their experiences with remote learning during the 2020 COVID-19 pandemic. In response to this crisis, remote learning was rapidly implemented and many BSW educators and students experienced online classrooms for the first time. Findings from this study shed light on how remote learning shapes the interpersonal relationships and communication that are so critical to building students’ sense of classroom belonging, engagement, and learning.
Keywords: dept.hls; dept.rec; dept.swk; peer-reviewed

Dimensions of burn survivor distress and its impact on hospital length of stay: A national institute on disability, independent living, and rehabilitation research burn model system study. - O'Brien, Kyle H (Burns : journal of the International Society for Burn Injuries, 2020)
OBJECTIVE: Guided by the Transactional Model of Stress and Coping, this study seeks to (1) examine the independent relationships between the level of distress among burn survivors, pre-morbid psychiatric history, and burn severity on length of hospital stay, and (2) to examine the relationship between having a premorbid psychiatric history and level of distress following a burn injury., METHODS: Data collected by the National Institute on Disability, Independent Living, Rehabilitation Research funded Burn Model System (N = 846) was used to theoretically link psychological distress with the length of hospital stay for survivors of burn injuries. Structural Equation Modeling was used to evaluate the aims of this study., RESULTS: Although counterintuitive, and while significant, burn severity was found to have a rather modest association with a burn survivor's level of distress, indicating that one's ability to cope may be a better predictor of distress rather than burn severity alone. Premorbid psychiatric history was significantly associated with increased levels of distress. While burn severity was associated with length of stay, level of distress did not act as a partial mediator. Length of stay was, however, significantly related to having a premorbid-psychiatric history. Of notable interest, a significant racial, ethnic, and gender difference exists in level of distress. Women and people of color experience higher levels of distress holding constant burn severity and psychiatric history., CONCLUSION: A need exists to assess for and address premorbid and current mental health challenges of burn survivors, specifically the ability to cope, especially among people of color and women, regardless of the burn size or severity. Copyright © 2019 Elsevier Ltd and ISBI. All rights reserved.
Keywords: *Adaptation, Psychological; *Burns/px [Psychology]; *Length of Stay/sn [Statistics & Numerical Data]; *Mental Disorders/px [Psychology]; *Psychological Distress; *Stress, Psychological/px [Psychology]; Adaptation, Psychological; Adolescent; Adult; African American; African Americans; African Americans/px [Psychology]; African Americans/sn [Statistics & Numerical Data]; Aged; Aged, 80 and over; Article; Body Surface Area; Burn survivors; Burns; Burns/ep [Epidemiology]; Burns/pa [Pathology]; Burns/pp [Physiopathology]; Caucasian; Distress; Ethnic Groups; European Continental Ancestry Group; European Continental Ancestry Group/px [Psychology]; European Continental Ancestry Group/sn [Statistics & Numerical Data]; Female; Hispanic; Hispanic Americans; Hispanic Americans/px [Psychology]; Hispanic Americans/sn [Statistics & Numerical Data]; Humans; Integrated care; Latent Class Analysis; Length of Stay; Length of stay; Male; Mental Disorders; Mental Disorders/ep [Epidemiology]; Mental health; Middle Aged; Models, Psychological; Psychological Distress; Psychosomatic; Sex Factors; Stress, Psychological; Stress, Psychological/eh [Ethnology]; Stress, Psychological/ep [Epidemiology]; Survivors; Young Adult; adolescent; adult; aged; body surface; burn; burn survivor; coping behavior; dept.hls; dept.hms; dept.rec; distress syndrome; electric burn; ethnic group; ethnology; female; hospital discharge; hospitalization; human; latent class analysis; length of stay; major clinical study; male; mental disease; mental stress; middle aged; outcome assessment; pain severity; pathology; pathophysiology; peer-reviewed; personal experience; psychiatric treatment; psychological aspect; psychological model; psychology; scald; secondary analysis; sex factor; structural equation modeling; survivor; very elderly; wound closure; young adult